Interleukin-33 Receptor (ST2) Deficiency Improves the Outcome of Staphylococcus aureus-Induced Septic Arthritis - Staurengo-Ferrari, Larissa; Trevelin, Silvia C.; Fattori, Victor; Nascimento, Daniele C.; de Lima, Kalil A.; Pelayo, Jacinta S.; Figueiredo, Florêncio; Casagrande, Rubia; Fukada, Sandra Y.; Teixeira, Mauro M.; Cunha, Thiago M.; Liew, Foo Y.; et al. (Frontiers in Immunology, 2018)
The ST2 receptor is a member of the Toll/IL-1R superfamily and IL-33 is its agonist. Recently, it has been demonstrated that IL-33/ST2 axis plays key roles in inflammation and immune mediated diseases. Here, we investigated the effect of ST2 deficiency in Staphylococcus aureus-induced septic arthritis physiopathology. Synovial fluid samples from septic arthritis and osteoarthritis individuals were assessed regarding IL-33 and soluble (s) ST2 levels. The IL-33 levels in samples from synovial fluid were significantly increased, whereas no sST2 levels were detected in patients with septic arthritis when compared with osteoarthritis individuals. The intra-articular injection of 1x107 CFU/10 microliters of S. aureus ATCC 6538 in wild-type (WT) mice induced IL-33 and sST2 production with a profile resembling the observation in the synovial fluid of septic arthritis patients. Data using WT, and ST2 deficient (-/-) and IFN-gamma-/- mice showed that ST2 deficiency shifts the immune balance towards a type 1 immune response that contributes to eliminating the infection due to enhanced microbicide effect via NO production by neutrophils and macrophages. In fact, the treatment of ST2-/- BMDM cells with anti-IFN-gamma abrogates the beneficial phenotype in the absence of ST2, which confirms that ST2 deficiency leads to IFN-gamma expression and and boosts the bacterial killing activity of macrophages against S. aureus. In agreement, WT cells achieved similar immune response to ST2 deficiency by IFN-gamma treatment. The present results unveil a previously unrecognized beneficial effect of ST2 deficiency in S. aureus-induced septic arthritis.